Performance of plant-based coagulants in removing turbidity and chemical oxygen demand (COD) in industrial wastewater: a systematic review and meta-analysis / Aimi Shazreen Shukri ... [et al.] - Shukri, Aimi Shazreen; Baharudin, Fauzi; Kassim, Jalina; Mohd Kamil, Nor Amani Filzah; Hamzah, Nurhidayah (2023)
Industrial effluent contains high concentrations of pollutants, such as heavy metals, which can cause risks to human health and the ecosystem. Chemical coagulants such as aluminum and iron salts are typically used as a coagulant in the wastewater treatment plant. The effectiveness of chemical coagulants is good in the clarification of wastewater, but excessive use is not sustainable and toxic. This study focuses on the removal of turbidity and chemical oxygen demand (COD) of various industrial effluents, including dairy wastewater, textile wastewater, paper, and paper mill industry, by comparing the removal between plant-based and chemical coagulants. The study aims to quantify the ability of plant-based coagulants to remove turbidity and COD in industrial effluents. A systematic review was used to conduct this study by using a systematic search strategy (PRISMA) in the relevant databases, which are Scopus, Web of Science, and Google Scholar. Only experimental studies that test both plant-based and chemical coagulants were chosen to proceed with meta-analysis to validate the efficiency of the plant-based coagulant to remove turbidity and COD in different industrial effluents by using Cochrane RevMan 5.4 software. Twenty-five articles were evaluated, and high heterogeneity was found among those studies. The mean difference (MD) and 95% confidence interval (CI) showed a significantly increasing percentage of turbidity and COD removal by plant-based coagulant by -1.64% (-3.49, 0.21) and -5.39% (-8.85, -1.93) respectively for all wastewaters. The result supports the application of plant-based coagulant to sustain wastewater treatment due to its eco-friendly, non-toxic, biodegradable, and capability to sustain the pH of water after treatment.